In vitro evaluation of the effect of different disinfectants on the biofilm of Staphylococcus epidermidis and Staphylococcus aureus formed on acrylic ocular prostheses - Moreno, Amália; dos Santos, Daniela Micheline [UNESP]; de Moraes Melo Neto, Clóvis Lamartine [UNESP]; de Melo Moreno, André Luiz; de Magalhães Bertoz, André Pinheiro [UNESP]; Goiato, Marcelo Coelho [UNESP] (Public Library of Science (PLoS), 2020)
The aim of this study was to evaluate the effect of disinfectants on the biofilm of Staphylococcus aureus and Staphylococcus epidermidis formed on the acrylic surface of ocular prostheses. In this study, 396 acrylic specimens were manufactured (50% for Staphylococcus epidermidis, and 50% for Staphylococcus aureus). For each bacterium, 66 specimens were subjected to biofilm formation on their surfaces for 24 hours, 66 specimens were subjected to biofilm formation on their surfaces for 48 hours, and 66 specimens were subjected to biofilm formation on their surfaces for 72 hours. Then, they were divided into groups according to disinfection method (n = 6): sterile distilled water for 10, 15, 30 min, and 6 hours (control); soap for 30 min (NES30); Opti-Free for 30 min (OPF30) and 6 h (OPF6); Efferdent for 15 min (EFF15); and 0.5%, 2%, and 4% chlorhexidine for 10 min (0.5% CHX10, 2% CHX10, and 4% CHX10). After the treatments, the specimens were vortexed to release the biofilm and the counting of bacterial colonies was performed (CFU/mL). Three-way ANOVA and the Tukey-Kramer HSD test were used (α = 0.05). For Staphylococcus epidermidis, there was no significant difference between NES30, OPF30, and OPF6 with their respective control groups; nor between NES30, OPF30, and OPF6 themselves, regardless of the biofilm development period (P >0.05). For Staphylococcus aureus, there was no significant difference between NES30 and OPF30 with their control group; nor between NES30 and OPF30 themselves, regardless of the biofilm development period (P >0.05). For Staphylococcus aureus, OPF6 showed a significant reduction in the number of CFU/mL when compared with its control group, NES30, and OPF30, regardless of the biofilm development period (P <0.05). For both bacteria, 0.5% CHX10, 2% CHX10,4% CHX10, and EFF15 showed a significant reduction in the number of CFU/mL when compared with their control groups, NES30, OPF30, and OPF6, regardless of the biofilm development period (P <0.05). Therefore, EFF15 and CHX (0.5%, 2% and 4%) were effective in reducing Staphylococcus epidermidis and Staphylococcus aureus on acrylic surfaces. NES30 and OPF (30 and 6) are not recommended.